ISLAMIC BROTHERHOOD IN SOCIAL MEDIA: A THEMATIC STUDY OF SURAH AL-HUJURAT VERSES 10–12 - Ahmad Ghozi Abdul Aziz; Jajat Sudrajat; Anzar Aquil (STAI Asy-Syukriyyah, 2026)
This study is motivated by the prevalence of destructive behavior on social media including cyberbullying, hoax dissemination, and religious polarization that threatens Islamic brotherhood (ukhuwah Islamiah). This study aims to indentify the values of ukhuwah Islamiah in QS. Al-Hujurat verses 10-12 and examine their relevance as ethical guidelines for muslims in social media use. Employing a qualitative library research approach with thematic interpretation (tafsir maudu’i), this study analyzes Tafsir Al-Misbah and Tafsir Ibnu Katsir. The findings reveal a comprehensive ethical framework: verse 10 affirms the theological foundation of brotherhood and islah, verse 11 prohibits sukhriyyah, al-lamz, and tanabuz bi al-alqab, while verse 12 forbids su’udzan, tajassus, and ghibah proven relevant as guidelines for responsible digital behavior aligned with Islam’s mission as rahmatan lil ‘alamin.